THE ROLE OF MODERN COMPUTER TECHNOLOGIES IN DIAGNOSIS AND TREATMENT OF ASTHMA - Atakhanov Sanjarbek Anvarovich; Madina Usmonjonova (Bright Mind Publishing, 2025)
This article discusses the role of modern computer technologies in the diagnosis and treatment of asthma. Additionally, the article provides information about asthma and its types. This article can be useful for students studying in the field of medicine as well as independent researchers.
Keywords: Asthmatic, persistent, intermittent, infection, bronchitis, personalization, biocamera, spirometry, influenza.